(3CMGOjK efJbGI ef CUhd SeGY GdMSf Hf eMeO Hf EHQGgje ef GdeMGaXGJ hGdYhGdis - (3CHh GdMSf SYO GdNjQ Hf eMeO Hf Sgd GdCfUGQjs; (3SYO GdNjQ Hf eMeO Hf Sgd Hf SYO GdCfUGQj GdCfOdSj, CHh GdMSf,J (B541 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdNjQ GdOhfi Yf CHj gQjQI QVi Gddg Yfg Cf QShd Gddg Udi Gddg Ydjg hSde bGd GdefHQ (B: (3Ef CUOb cdeI JcedJ Hg GdYQH cdeI dHjO s
(3BNQgG (B:s
(3ef TYQ CSYO Hf Ydi GdRhRfi EPG cGf GdReGf ReGf ShA ajhe UGdM efg ZfjeI s
(3HBNQgG bQGAI SfI (B651 (3hSfI (B663 s
(3hUhQI SeGY ef GdCUd GdefJSN efg SfI (B594s
(3QhGjI aNQ GdfSGA aGWeI HfJ SYO GdNjQ GdePchQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B84s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs